1992
DOI: 10.1104/pp.98.1.287
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose Metabolism in Tubers of Potato (Solanum tuberosum L.)

Abstract: Excision of developing potato (Solanum tuberosum L.) tubers from the mother plant, followed by storage at 10°C, resulted in a rapid, substantial decrease in sucrose synthase activity and considerable increases in hexose content and acid invertase activity. A comparison of the response of three genotypes, known to accumulate different quantities of hexoses in storage, showed that both sucrose synthase activity and the extent to which activity declined following excision were similar in all cases. However, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…They could encode proteins of 805 amino acids with calculated molecular masses of ~92 kD, which is consistent with the estimated size of 90 kD for potato sucrose synthase (Ross and Davies, 1992 The presence of a long leader intron in the 5' untranslated region is a typical feature of sucrose synthase genes (Werr et al, 1985;Chopra et al, 1992;Wang et al, 1992;Yu et al, 1992;Shaw et al, 1994). A 1612-bp leader intron with a GT/AG splicing boundary was easily identified in Sus4-16 by comparing its sequence with that of the 5' untranslated region of the potato sucrose synthase cDNA Pofssyn (Figure 4).…”
Section: Identification Of the Coding Sequences In Representative Sussupporting
confidence: 50%
See 1 more Smart Citation
“…They could encode proteins of 805 amino acids with calculated molecular masses of ~92 kD, which is consistent with the estimated size of 90 kD for potato sucrose synthase (Ross and Davies, 1992 The presence of a long leader intron in the 5' untranslated region is a typical feature of sucrose synthase genes (Werr et al, 1985;Chopra et al, 1992;Wang et al, 1992;Yu et al, 1992;Shaw et al, 1994). A 1612-bp leader intron with a GT/AG splicing boundary was easily identified in Sus4-16 by comparing its sequence with that of the 5' untranslated region of the potato sucrose synthase cDNA Pofssyn (Figure 4).…”
Section: Identification Of the Coding Sequences In Representative Sussupporting
confidence: 50%
“…In contrast, Sus3 transcripts were not sucrose inducible and were present at relatively constant low levels after incubation with various concentrations of sucrose. Ross and Davies (1992) have shown that tuber excision causes a rapid decrease in both the amount and activity of sucrose synthase. As expected, we found that the Sus4 class transcript level decreased dramatically within 6 hr after tuber excision and was almost undetectable after 12 hr ( Figure 9C).…”
Section: Sus3 and Sus4 Genes Are Differentially Expressedmentioning
confidence: 99%
“…The tetrameric structure of the native protein is similar to that observed with mung bean seedlings (10), rice grains (15), maize kernels (21), soybean nodules (14), and peach fruit (13). In these instances, the molecular mass of the protein ranges between 360 and 400 kD, with the molecular masses (18). The amino acid sequence data, although only for a small portion of the faba bean SS protein, show distinct homology with potato tuber SS, which itself has a 75% overall identity with maize SS (20).…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the purification, SS activity was assayed in the cleavage direction (18). Additionally, sucrose cleavage activity with nucleoside diphosphates other than UDP was determined using a stopped assay system.…”
Section: Enzyme Assaymentioning
confidence: 99%
“…2, curve D). Because invertase activity is virtually absent in WT tubers during loading (Ross and Davies 1992), an endogenous invertase cannot be responsible for oligosaccharide synthesis in the rolC invertase/WT combinations, thus ruling out the possibility of oligosaccharide synthesis in the tubers of rolC invertase/WT grafts. This shows that oligosaccharides produced in the companion cells of above-ground plant tissues have been transported via the phloem to the storage organs in an apoplastic loader.…”
Section: Graft Experiments Revealed Long-distance Transport Of a Trismentioning
confidence: 94%